ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA KELAS VIII MTs NEGERI KUPANG - Syahriyati Jamila Ibrahim; St Muthmainnah Yusuf; Ryan Nizar Zulfikar (MEGA: Jurnal Pendidikan Matematika, 2020)
This research aims to find out the mathematical literacy skills of grade VIII students of MTs Kupang State School Year 2019/2020. This type of research is descriptive research with a qualitative approach. The subjects of the study were 30 students grade MTs Kupang State School Year 2019/2020. The object of this research is the mathematical literacy ability of students grade MTs Kupang State School Year 2019/2020. Data collection techniques with tests using essay tests. Instruments used in research are essay type tests, interviews and documentation. The data analysis techniques used are three, namely, data reduction, data presentation, and drawing conclusions. Test the validity of the data in this study using triangulation techniques. From the results of the study shows that the results of the calculation of the percentage of students who are able to reach KKM as much as 40% while students who do not reach KKM as much as 60%, thus it is concluded that the mathematical literacy ability of grade MTs Kupang state is still low because in this class there are still many students who are weak on formulating and planning strategies in solving problems.